THE INFLUENCE OF LEADERSHIP AND WORK MOTIVATION ON THE PERFORMANCE OF KODIM 0103/NORTH ACEH SOLDIERS WITH ORGANIZATIONAL COMMITMENT AS INTERVIENING VARIABLES IN HANDLING OF ROHINGYA REFUGEE IN LHOKSEUMAWE CITY - Kistiyanto, Oke; Marbawi, Marbawi; Dharma, Yulius (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
This study examines the influence of leadership and work motivation on the performance of Kodim 0103/Aceh Utara soldiers carrying out its missions with organizational commitment as intervening variable in handling of Rohingya refugees in Lhokseumawe City in 2020. The sample uses 115 people with purposive sampling as the sampling technique. The sample criteria are Kodim 0103/North Aceh soldiers who were involved in handling Rohingya refugees in Lhokseumawe City from June to December 2020. Data analysis using WarpPLS 8.0 software with Structural Equation Modeling (SEM) analysis method accompanied by Partial Least Square (PLS) approach. The results showed that the three research variables namely leadership, work motivation and organizational commitment had a positive and significant effect on the performance of Kodim 0103/North Aceh soldiers. Moreover, the result of the study also show that the organizational commitment variable partially mediated the relationship between leadership and work motivation on soldiers’ performance in relation to handling Rohingya refugees in Lhokseumawe city in 2020.